Quantitative analysis of the risk of hydrogen sulfide release from gas hydrates - Wang, Xianqing; Liu, Siqing; Zhao, Bin; Yao, Yanfu; Wu, Gang; Xie, Rui; Fu, Yutong; Ning, Zijie (Frontiers in Earth Science, 2023)
The role that H2S plays in the global sulfur cycle has been studied extensively in recent years. This paper focuses on the influence of H2S released from gas hydrates on sulfur cycle and establishes a one-dimensional mathematical model to calculate the amount of H2S released from the dissociation of gas hydrates present in multiple layers in the Qiongdongnan Basin China. The results show that the sulfate and methane transition zone that covers an area of about 100 km2in the Qiongdongnan Basin contains 2.3 × 1012 g of pyrite, which requires 4.06 × 1011 mol of H2S for its formation. The H2S released from the dissociation of gas hydrates is 5.4 ×1011 mol, which is about 1.3 times that needed for the formation of pyrite. Therefore, the H2S released from the gas hydrates is an important source of H2S for the formation of pyrite in the sulfate-methane transition zone of Qiongdongnan Basin. According to the flux of H2S and the partial pressure of O2 (PO2) in the atmosphere, the critical value of the balance between the flux of H2S and PO2 turns out to be 0.13 mol kg−1∙bar−1. Furthermore, considering the effect of global sea-level changes, three risk modes are identified to categorize the amount of H2S released from the dissociation of gas hydrate into the atmosphere. We classify the periods from 5–12 Ma BP, 25–29 Ma BP, 47–52 Ma, and 57–61 Ma BP into the high-risk mode. Furthermore, the results show that a part of the H2S released from the gas hydrate dissociation is oxidized by the Fe (III) oxide metal, with much of the metal ions being released into the pore water. Another part of the H2S is re-oxidized by the O2 in the ocean, with much of SO42- released into the seawater. Therefore, the process also provides metal ions and SO42- to pore water or seawater when the H2S released from gas hydrate diffuses from the bottom. This paper provides new insights into the source of H2S in the ocean and shows that the H2S contained in gas hydrates plays an important role in the global sulfur cycle.